Study of N, P, K Nutrient Uptake In Rice Plants With Total Soil Microbes In Sei Nahodaris Village, Panai Tengah District, Labuhanbatu Regency - Rauf, Abdul; Syawal, Fitra; Siagian, M. yusuf (Jurnal Online Pertanian Tropik, 2023)
The physical, chemical and biological quality of the soil has deteriorated due to the excessive use of chemical fertilizers in paddy fields and neglect to return organic matter to the soil. Populations of soil biota involved in nitrogen fixation and phosphate solubility decrease below this. The purpose of this study was to determine the relationship between rice plants in Satiman, Sei Nahodaris Village, Panai Tengah District, Labuhan Batu Regency, and nutrient uptake of N, P, and K. This research was conducted from October to December 2022. In paddy fields, five zigzag sampling points were used to collect rice plant leaves and rhizosphere soil for sampling. Nutrient uptake of N, P, and K, in addition to total microbial, were the parameters analyzed in this study. The direct Pearson correlation method was used to perform the analysis. Analysis showed that sampling point number 5 had the highest microbial population, namely 9.53 x 106.N, P, and K absorbed at an average of 3.51 percent (optimum), 0.27 percent (excess), and 1.306 percent (optimum). The relationship between total soil microbes and N, P, and K uptake is weak and negative (-0.212) with a closeness of 4.50 percent; very high (0.94) and positive with a closeness level of 88 percent; it is moderate and negative; and weak and negative.-0.46), with a similarity level of 21 percent. So it can be said that phosphate solubilizing bacteria dominate soil microbes in rice plants in Sei Nahodaris Village, Panai Tengah District, Labuhan Batu